MERGER IN ISLAMIC BANKING SECTOR: A SNAP OF VIEWS FROM THEIR CUSTOMERS AND PROSPECTIVE CUSTOMERS - Fitri Purnamasari; Hanjar Ikrima Nanda; Muhammad Zulkarnaen Purnamaputra; Margareta Susanti; Mohd. Rizal Palil (International Journal of Social Science, 2022)
Various kinds of strategies tend to be carried out by the perpetrators’ business to maintain effort at a time strengthen position in the middle competitors others, such as carry out a strategy of merging effort or mergers. However, a merger also has an impact on the internal parties of the entities that do. This study attempted for dig more in about the views of banking customers and prospective customers from Bank Syariah Indonesia (BSI) after the merger process. We use qualitative method and collected the research data from open questionnaire and interview from 81 banking customers and prospective customers of 3 ex-BSI Islamic Banks in Malang City. They responded to this merger as a positive phenomenon, although there are also some things to worry about.